Desempenho térmico de radiador protótipo para resfriamento radiativo noturno - Trento, Daniel Gustavo (2021)
This study focuses on the thermal characterization of prototype radiators developed and manufactured for nocturnal radiative cooling as a passive way of cooling buildings. For this purpose, the study had three phases. First, the analytical method helped to analyze the nocturnal radiative cooling potential of a surface exposed to the local atmospheric conditions. Then, a field experiment with a system made of 0.78 m² prototype radiators was developed. The panels were connected to a 200 l main water tank and an intermediate 30 l tank. The enclosed system also had a low power pump working from 18h and 6h in the following morning, between 9 and 12 February 2021. The third phase addressed a numerical method via computational fluid dynamics (CFD) simulations. The same environmental data collected in the field experiment were used as input to predict the radiators’ thermal behavior. The comparison of the experiment’s results to the analytical’s and the simulations’ ones by mean of correlational data analysis shows that the theoretical cooling achieved by the analytical method enabled the definition of the maximum nocturnal radiative cooling potential. Likewise, the simulations’ results allowed the prediction of the thermal behavior of the prototype radiators under the same climatic conditions. The CFD simulations also enabled the identification of a steep decline in temperature in the initial stretch inside the prototype radiator and its stagnation in the remaining water path. To verify such thermal behavior, thermal images were made of the working system that confirmed the simulation result. Thus, a change in the radiators’ design was proposed to ensure a shorter water path by adopting a parallel arrangement for the water channels. Computational simulations showed that this arrangement resulted in improved thermal performance of up to 9.6% during the nighttime. Finally, the new arrangement with 3 meters water path was simulated with different water flow rates. In conclusion, the study showed that the use of CFD simulations is a viable alternative to determine the radiators arrangement’s and design’s thermal efficiency for nocturnal radiative cooling. Shorter water paths within the radiator’s channels increase cooling rate and thermal efficiency and the increment in their length only improves thermal performance when the wind speed is relevant.